2017
DOI: 10.3346/jkms.2017.32.2.310
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and Phenotype Analysis in Pediatric Patients with Cystinuria

Abstract: Cystinuria is an inherited disorder characterized by defective renal reabsorption of cystine and dibasic amino acids leading to nephrolithiasis. This study was conducted to analyze the genotypes and phenotypes of pediatric patients with cystinuria. Eight children from Seoul National University Hospital and Asan Medical Center presenting with cystinuria from January 2003 to June 2016 were retrospectively analyzed. Mutational studies were performed by direct sequencing. Two of the 8 were male and 6 were female. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
3
10
0
1
Order By: Relevance
“…found no significant differences in multiple clinical parameters, such as age at disease presentation or number of urolithiasis episodes when comparing groups of patients with different genotypes [ 10 ]. Similar data were reported for Korea, Czechia, Slovakia, and Greece [ 9 , 14 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…found no significant differences in multiple clinical parameters, such as age at disease presentation or number of urolithiasis episodes when comparing groups of patients with different genotypes [ 10 ]. Similar data were reported for Korea, Czechia, Slovakia, and Greece [ 9 , 14 ].…”
Section: Discussionsupporting
confidence: 87%
“…Despite this, coverage of most parts of Poland was maintained and thus the cohort is representative of the whole country, ensuring that the results obtained were not biased. In addition, the number of observations from the clinical national data is comparable to those reported in previous studies from Korea, Portugal, France [ 8 ], and Great Britain [ 9–12 ]. All clinical pediatric research centers dealing with tubulopathies in Poland were engaged in the study, making the clinical analysis of pediatric cystinuria patients the first and largest of its kind in Poland.…”
Section: Discussionsupporting
confidence: 80%
“…42 Inherited metabolic disorders are often associated with pediatric urolithiasis cases. 43 Adenine phosphoribosyltransferase deficiency, 44 cystinuria, [45][46][47] xanthinuria, 48 Dent disease, 49,50 familial hypomagnesemia with hypercalciuria and nephrocalcinosis, 51,52 and primary hyperoxaluria [53][54][55] cause urinary hypersaturation of insoluble mineral salts, which can inevitably increase the risk of kidney stone formation (LE:4).…”
Section: Commentarymentioning
confidence: 99%
“…In many studies, it has been reported that there is no genotype-phenotype correlation in patients with cystinuria, and also no mutation is shown in 5% of patients. 12,13 Therefore, detection of increased urinary cystine excretion still remains the main tool in assessing the prognosis and deciding on appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%